Implementation of the K-Medoids Clustering Method in Grouping Districts in Sleman Regency, Yogyakarta According to the Amount of Fruit Production in 2023 - Wijayati, Puspa Chandra; Kariyam, Kariyam (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Agriculture is one of the main factors in economic development in Indonesia, as Indonesia is an agrarian country. The government also expects agricultural production of food crops to increase every year. This study aims to determine the clustering results and characteristics of each sub-district in Sleman Regency based on the amount of fruit production. The method used in this research is K-Medoids Clustering. The K-Medoids method includes a clustering algorithm that is quite efficient in clustering small data and finding the most representative points and being able to overcome outliers. The results showed the application of the K-Medoids method resulted in 5 clusters where Cluster 1 has 4 sub-districts namely, Moyudan, Minggir, Seyegan, and Godean sub-districts, Cluster 2 has 5 sub-districts namely, Gamping, Mlati, Depok, Berbah, and Prambanan sub-districts, Cluster 3 has 4 sub-districts namely, Kalasan, Ngemplak, Ngaglik, and Sleman sub-districts, Cluster 4 has 2 sub-districts namely, Tempel and Turi sub-districts, and Cluster 5 has 2 sub-districts namely, Pakem and Cangkringan sub-districts.